Drogi kształtowania się francuskiej klasy średniej - Leoński, Jacek (Wydział Prawa i Administracji UAM, 1982)
The modern French middle class is an interesting research subject. The problem of the historical and sociological ways of its developement and transformations is also engaging. The French middle class has its roots in the revolutionary changes of the late 18 century, but its fundamental part was formed in the second half of the 19 century and in the first half of the present century. Two stages of the French middle class formation can be distinguished: the first one,, related to the Belle Epoque, lasting conventionally to 1914 and the second one opening with the outbreak of the World War I. The great bourgeoise and the working class were rising and developing in the Belle Epoque period, the social role of the middle class also increased. The latter was in a way filling the lacunae which emerged between the other classes. The French middle class of that period was described as "capacités". It was composed mostly of professional lawyers (judicial officers, attorneys, notaries) and medical doctors. These professional categories had often a tradition of several generations and their material existence was based on fees received from their individual clients. Apart of these categories, the group of "capacités" comprised professionals salaried by the state, private enterprises and various other institutions. Engineers, journalists, scientifis and education workers have to be named here. A social importance of the "capacités" diminished in the interwar period, the „new middle class"-„les cadres" started seizing their position, they were to rise in power in the social life after the World War II. A period of its social developement and stabilization was closed at the beginning of the sixties.
The Directions of Forming the French Middle Class